Public key cryptography using sphere and spheroid. (2018) - Singh, K. John; Gagneja, Kunal
Encryption has different requirements such as speed and immunity to side channel attacks. In this paper, a novel mechanism for public key encryption is proposed. It is faster and has inbuilt compression. Experiments are carried out with video, high definition video and image files. Results when compared with various encryption algorithms indicate that the proposed cryptosystem has a stronger and faster architecture. The proposed algorithm can be modified to work both as a block and stream cipher. Generally, block cipher increases the size of ciphertext due to padding. Such phenomenon is lesser observed in the proposed cipher. It makes cipher convenient for resource constraint networks. Most of the symmetric key algorithms have XOR and shuffling in their blocks. This is one of the reasons why they have similar kind of vulnerabilities. Spheroid cryptosystem proved to be at least 77.2% faster than other algorithms.